2018
DOI: 10.1128/mcb.00243-18
|View full text |Cite
|
Sign up to set email alerts
|

The N Termini of TAR DNA-Binding Protein 43 (TDP43) C-Terminal Fragments Influence Degradation, Aggregation Propensity, and Morphology

Abstract: Fragments of the TAR DNA-binding protein 43 (TDP43) are major components of intracellular aggregates associated with amyotrophic lateral sclerosis and frontotemporal dementia. A variety of C-terminal fragments (CTFs) exist, with distinct N termini; however, little is known regarding their differences in metabolism and aggregation dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…In addition to the neuronal terminal differentiation deficits and gliosis in Vps35 Neurod6 mice, we also detected increases of P62/sequestosome 1 (SQSTM1), one factor that targets specific cargoes for autophagy, and Tdp-43, a DNA-RNA binding protein, in Vps35 Neurod6 cortical neurons (Figure 4) [33][34][35][36], both proteins often associated with the pathology of FTD [21,37]. To determine if expressing VPS35-mCherry fusion protein could reduce this brain pathology in Vps35 Neurod6 mice, we performed both coimmunostaining and Western blot analyses.…”
Section: Partial Reduction Of P62 and Tdp43 Proteins In Tgvps35 Neurod6 ; Ko Pubsmentioning
confidence: 90%
“…In addition to the neuronal terminal differentiation deficits and gliosis in Vps35 Neurod6 mice, we also detected increases of P62/sequestosome 1 (SQSTM1), one factor that targets specific cargoes for autophagy, and Tdp-43, a DNA-RNA binding protein, in Vps35 Neurod6 cortical neurons (Figure 4) [33][34][35][36], both proteins often associated with the pathology of FTD [21,37]. To determine if expressing VPS35-mCherry fusion protein could reduce this brain pathology in Vps35 Neurod6 mice, we performed both coimmunostaining and Western blot analyses.…”
Section: Partial Reduction Of P62 and Tdp43 Proteins In Tgvps35 Neurod6 ; Ko Pubsmentioning
confidence: 90%
“…The N-terminal region of each TDP-43 CTF may determine the specific pathway through which it is degraded (Kasu et al, 2018). Arginyltransferase (ATE), the enzyme responsible for post-translational arginylation, has been implicated in signaling processes required for the degradation of intracellular proteins by autophagy or UPS pathways.…”
Section: Degradation and Cellular Clearance Of Tdp-43 Ctfsmentioning
confidence: 99%
“…When expressed in mouse fibroblasts deficient for ATE, TDP-43 CTFs aggregate, suggesting that they are selectively degraded by the Arg/N-end rule pathway as a protective response to failing proteostasis and neurodegeneration (Brower et al, 2013). More recent work has shown that, whereas TDP-43 fragments beginning at residue 247 are degraded primarily by the Arg/N-end rule pathway, degradation of fragments with an N-terminal at residue 219 can occur independently of ATE (Kasu et al, 2018). Further dissection of the precise mechanisms of degradation of the different TDP-43 CTFs and the role of ATE is therefore warranted.…”
Section: Degradation and Cellular Clearance Of Tdp-43 Ctfsmentioning
confidence: 99%
“…Other than the LCD, a segment of RRM2 ( 247 DLIIKGISVHI 257 ) has been shown to form several steric zipper polymorphs (Guenther et al, 2018b), suggesting this domain may also contribute to pathological aggregation at least when RRM2 is partially folded (Tavella et al, 2018). Additionally, the size of the TDP-43 fragments (35 kDa or 25 kDa) influences the aggregation and degradation pathways of TDP-43 (Kasu et al, 2018). On the other hand, the majority of evidence for TDP-43 to form amyloid comes from purified protein studies utilizing C-terminal fragments that are either pathological fragments (35 or 25 kDa) or just the LCD (amino acids 274–414), as well as just the RRMs or small segments thereof (Guenther et al, 2018b; Agrawal et al, 2019; Cao et al, 2019).…”
Section: Tdp-43 Prion Evidencementioning
confidence: 99%